Investigating cell-specific effects of FMRP deficiency on spiny projection neurons in a mouse model of Fragile X syndrome - Giua, Gabriele; Lassalle, Olivier; Makrini-Maleville, Leila; Valjent, Emmanuel; Chavis, Pascale; Manzoni, Olivier J. J. (Frontiers in Cellular Neuroscience, 2023)
Introduction Fragile X syndrome (FXS), resulting from a mutation in the Fmr1 gene, is the most common monogenic cause of autism and inherited intellectual disability. Fmr1 encodes the Fragile X Messenger Ribonucleoprotein (FMRP), and its absence leads to cognitive, emotional, and social deficits compatible with the nucleus accumbens (NAc) dysfunction. This structure is pivotal in social behavior control, consisting mainly of spiny projection neurons (SPNs), distinguished by dopamine D1 or D2 receptor expression, connectivity, and associated behavioral functions. This study aims to examine how FMRP absence differentially affects SPN cellular properties, which is crucial for categorizing FXS cellular endophenotypes. Methods We utilized a novel Fmr1−/y::Drd1a-tdTomato mouse model, which allows in-situ identification of SPN subtypes in FXS mice. Using RNA-sequencing, RNAScope and ex-vivo patch-clamp in adult male mice NAc, we comprehensively compared the intrinsic passive and active properties of SPN subtypes. Results Fmr1 transcripts and their gene product, FMRP, were found in both SPNs subtypes, indicating potential cell-specific functions for Fmr1. The study found that the distinguishing membrane properties and action potential kinetics typically separating D1- from D2-SPNs in wild-type mice were either reversed or abolished in Fmr1−/y::Drd1a-tdTomato mice. Interestingly, multivariate analysis highlighted the compound effects of Fmr1 ablation by disclosing how the phenotypic traits distinguishing each cell type in wild-type mice were altered in FXS. Discussion Our results suggest that the absence of FMRP disrupts the standard dichotomy characterizing NAc D1- and D2-SPNs, resulting in a homogenous phenotype. This shift in cellular properties could potentially underpin select aspects of the pathology observed in FXS. Therefore, understanding the nuanced effects of FMRP absence on SPN subtypes can offer valuable insights into the pathophysiology of FXS, opening avenues for potential therapeutic strategies.